Effect of grain size on rotary swaging of sintered tungsten rod - Shaoxin Zhou (Elsevier, 2021)
Tungsten has poor processing performance and its brittleness often leads to defects. The effect of grain size on rotary swaging of the sintered rod was investigated to improve the quality of the destination part. Three different grain sizes of sintered rods were selected to research the physical and mechanical properties, microstructure, and texture. The texture evolution of the sintered rods and the effect of qualification rate of destination parts were studied. It was found that the {111}<uvw> texture existed in the sintered samples along with the γ fiber. With the increase of grain size, the hardness decreased gradually, the intensity of {111}<uvw> became weak, and γ fiber was no longer complete. Meanwhile, this work investigated the evolution of sintered texture on subsequent processing. The results showed that the sintered texture evolved into {111}<110> after rotary swaging, and the fiber texture of <110> became the main texture after drawing. The {111}<uvw> texture formed in the sintered process was not beneficial to ductility. The increment of grain size has advantages for the processing technology within a certain range.